2011
DOI: 10.1186/1476-4598-10-83
|View full text |Cite
|
Sign up to set email alerts
|

The human RECQ1 helicase is highly expressed in glioblastoma and plays an important role in tumor cell proliferation

Abstract: BackgroundRecQ helicases play an essential role in the maintenance of genome stability. In humans, loss of RecQ helicase function is linked with predisposition to cancer and/or premature ageing. Current data show that the specific depletion of the human RECQ1 helicase leads to mitotic catastrophe in cancer cells and inhibition of tumor growth in mice.ResultsHere, we show that RECQ1 is highly expressed in various types of solid tumors. However, only in the case of brain gliomas, the high expression of RECQ1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 49 publications
5
55
0
Order By: Relevance
“…8). Consistently, downregulation of RECQ1 was shown to trigger spontaneous Rad51 foci formation and an increase in SCEs, 35,36 and this is also consistent with the finding that RECQ1 mouse embryonic fibroblasts (MEFs) are associated with chromosomal instability and an increase in the frequency of SCEs. 51 HR-mediated repair of broken replication forks can particularly result in the blockage of leading-strand extensions in the presence of bulky lesions.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…8). Consistently, downregulation of RECQ1 was shown to trigger spontaneous Rad51 foci formation and an increase in SCEs, 35,36 and this is also consistent with the finding that RECQ1 mouse embryonic fibroblasts (MEFs) are associated with chromosomal instability and an increase in the frequency of SCEs. 51 HR-mediated repair of broken replication forks can particularly result in the blockage of leading-strand extensions in the presence of bulky lesions.…”
Section: Discussionsupporting
confidence: 69%
“…Our results are consistent with the previous observations that transient depletion of RECQ1 affected cell proliferation. [34][35][36][37] Next, we wanted to analyze the sensitivity patterns of RECQ1 depletion. Using the two independent lentiviral shRNA constructs, depletion of RECQ1 was performed in both HeLa (Fig.…”
Section: Recq1mentioning
confidence: 99%
“…As described previously, RECQ helicases comprise a highly conserved family of DNA helicases that operate to maintain genomic DNA stability in humans [20]. Defects in human RECQ helicases are associated with premature aging, genome instability, and cancer predisposition [21].…”
Section: Discussionmentioning
confidence: 98%
“…RECQ1 silencing in cancer cells resulted in mitotic catastrophe and injection of siRNA targeting RECQ1 prevented tumor growth in murine models (54)(55)(56). More recently, it was shown that RECQ1 is highly expressed in various types of solid tumors including colon carcinoma, thyroid cancer, lung cancer, and brain glioblastoma tissues (57). In glioblastoma cell lines, depletion of RECQ1 by RNA interference results in a significant reduction of cellular proliferation, perturbation of S-phase progression, spontaneous g-H2AX foci formation, and hypersensitivity to hydroxyurea and temozolomide treatments (57).…”
Section: Discussionmentioning
confidence: 99%